Centralized inventory and supply chain management of Manila's rice dealers - Cancio, Alliah Zean B. Clutario, Ela Rose S. De Guzman, Bryle Jencel, De Leon, Candice P. Remetio, Deciry I. Roga, Rodelyn N. 4 0 16; 5 (2024)
ABSTRACT The rice industry played an important role in the Philippines, serving as a staple food source for the nation. However, the industry faced intricate challenges, necessitating a comprehensive examination of the interplay between supply chain management, inventory systems, and the practices of rice dealers in Manila. This study investigates the adoption and effect of centralized inventory systems (CIMS) among rice dealers and wholesalers in Manila, Philippines. The research aimed to understand the factors influencing the adoption of CIMS and its effect on supply chain management, inventory control, and overall operational efficiency. The study employs a quantitative approach with a descriptive research design and utilizes surveys to collect data from rice dealers in Manila. The findings reveal that the adoption of CIMS was influenced by factors such as income, location, years of experience, and business size. The implementation of CIMS leads to improvements in inventory control, supply chain performance, and operational performance. However, the effects of CIMS varies across demographic factors, suggesting a need for targeted strategies to promote its adoption among all rice businesses. The study concludes that CIMS offers significant benefits for rice dealers and wholesalers in Manila, improving inventory control, supply chain performance, and overall operational efficiency.
Business Research: (BSBA major in Operations Management) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2